2015
DOI: 10.1186/s12941-015-0098-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of extended-spectrum beta-lactamases (ESBLs) produced by clinical isolates of Acinetobacter baumannii in Saudi Arabia

Abstract: BackgroundAcinetobacter baumannii is a common opportunistic pathogen that causes major nosocomial infections in hospitals. In this study, we hypothesized a high prevalence of A. baumanni ESBL (extended-spectrum beta-lactamase) among all collected isolates.MethodsA. baumannii isolates (n = 107) from ICU (Intensive care unit) of local hospitals in Makkah were phenotypically and genotypically characterized. The identity and antibiotic susceptibility of A. baumannii strains were determined using the Vitek-2 system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 46 publications
5
44
1
2
Order By: Relevance
“…Due to the widespread dissemination among nosocomial pathogens via plasmids and integrons, ESBL genes can cause further expansion of drug resistance, including MDR isolates (14,24). Various studies have reported frequencies of ESBL genes in A. baumannii ranging from 25% to 93.45% (25)(26)(27)(28). In the present study, among the 80 examined isolates of A. baumannii, 53.8% were ESBL producers, which is consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Due to the widespread dissemination among nosocomial pathogens via plasmids and integrons, ESBL genes can cause further expansion of drug resistance, including MDR isolates (14,24). Various studies have reported frequencies of ESBL genes in A. baumannii ranging from 25% to 93.45% (25)(26)(27)(28). In the present study, among the 80 examined isolates of A. baumannii, 53.8% were ESBL producers, which is consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…(84%) whereas, Alyamani et al, reported (94%). [25] The second higher producer of ESBL was Pseudomonas aeruginosa (73.07%), in contrast Shaikh et al, reported 25.13% ESBL prevalence, which is much lower than our finding. [26] This shows a rising trends of ESBL in these days and the reason may be indiscriminate and rampant use of cephalosporins for the treatment of common infections, as well as horizontal transmission of resistant genes among hospital acquired bacterial strains.…”
Section: Discussioncontrasting
confidence: 56%
“…The prevalence of imipenem-resistance among A. baumannii isolates was 99%. This rate is very high compared to resistance rates of clinical isolates reported few years ago from Jordan and neighboring countries which ranged between 90% to 64% [3,31,32,33]. A previous Jordanian study has also indicated that majority of Abaumannii isolates from environmental and clinical sources was multidrug resistant, except for colistin and tigecycline similar to the case in other countries such as Lebanon [3,32].…”
Section: Discussionmentioning
confidence: 68%